Theoretical Study on Structural Stability of Alloy Cages: A Case of Silicon-Doped Heterofullerenes (Communications in Computational Physics, 2010)
Structural stability and Si-substitution pattern in fullerene cage of C60−nSin are thoroughly investigated by integrating density functional calculations with a colorbondgraph (CBG) model. We find that the parameterized CBG model with genetic algorithmscan efficiently scan the large configuration space of alloy and therefore identifythe low-energy region within the first-principles accuracy. Low-energy (stable)structures of C60−nSin in carbon-rich region (1≤n≤30) were identified and the siliconatoms are found to tend to aggregate in the fullerene cage. The mixing energy of theselow-energy structures is ∼ 35 meV/atom and insensitive to the Si concentration. Weexpect that these alloy fullerene cages can be synthesized experimentally at elevatedtemperatures.